The Effectiveness of a Creative Approach Combining PBL and NHT Models in Biology Learning to Improve Critical Thinking Skills - Arlian Firda; Yulia Syafitri (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to determine the effectiveness of a creative learning approach combining the Problem Based Learning (PBL) and Numbered Head Together (NHT) models in improving students’ critical thinking skills in biology learning. This study was conducted due to the low level of students’ critical thinking skills caused by the dominance of conventional learning methods that limit students’ active participation. A quasi-experimental method with a non-equivalent control group design was employed. The sample consisted of two tenth-grade classes at SMA Negeri 2 Pekanbaru selected through purposive sampling, with class X.2 as the experimental class and class X.9 as the control class, each consisting of 36 students. Data were collected using pretest and posttest instruments based on critical thinking indicators and observation sheets of teacher and student activities. The results showed that the experimental class obtained higher mean pretest and posttest scores (70.65 and 86.94) than the control class (63.43 and 80.00). The N-gain analysis indicated that both classes were in the moderate category; however, the experimental class achieved a higher N-gain score (0.58) compared to the control class (0.48). The t-test results revealed a significant difference between the two classes (Sig. = 0.016 < 0.05). The integration of PBL and NHT promotes active learning, collaboration, and problem-solving processes that support the development of students’ critical thinking skills. In conclusion, the creative approach combining PBL and NHT is effective in enhancing students’ critical thinking skills and biology learning outcomes.